2020
DOI: 10.1177/0963689720960174
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Hsa_circ_002178 Promotes the Growth and Migration of Breast Cancer Cells and Maintains Cancer Stem-like Cell Properties Through Regulating miR-1258/KDM7A Axis

Abstract: Breast cancer (BrCa) is the most common malignancy in women. Accumulating evidence demonstrated that abnormal circRNA expression is associated with the occurrence and progression of tumors. We analyzed the GSE101123 data and found that the expression of hsa_circ_002178 (circ_002178) was significantly increased in BrCa tissues. However, the role and possible underlying mechanisms of circ_002178 in BrCa still remain unrevealed. In this investigation, the expression levels of circ_002178 in cancer tissues or BrCa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Cut-off values of high or low circRNA expression were mostly median or mean.The range of mean duration of follow□up was from 30 to 250 months.Moreover,Detection methods of circRNA expression were mainly quantitative real□time polymerase chain reaction (RT□PCR).Sample types were almost from tissues. As for clinical outcome indicators, 27 studies[10, 11, 13-34],[35-37]included overall survival (OS), 5 studies[19, 29, 31, 33, 38]included disease-free survival (DFS).As shown in Table 3, nineteen types of circRNAs were recognized as tumor promoters and nine were tumor suppressors. 28 circrnas have corresponding targets and can promote or inhibit the proliferation, invasion and metastasis of breast cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…Cut-off values of high or low circRNA expression were mostly median or mean.The range of mean duration of follow□up was from 30 to 250 months.Moreover,Detection methods of circRNA expression were mainly quantitative real□time polymerase chain reaction (RT□PCR).Sample types were almost from tissues. As for clinical outcome indicators, 27 studies[10, 11, 13-34],[35-37]included overall survival (OS), 5 studies[19, 29, 31, 33, 38]included disease-free survival (DFS).As shown in Table 3, nineteen types of circRNAs were recognized as tumor promoters and nine were tumor suppressors. 28 circrnas have corresponding targets and can promote or inhibit the proliferation, invasion and metastasis of breast cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, our study displayed that the hsa_circRNA_002178 level was rose in HCC. It has been reported that hsa_circRNA_002178 was upregulated in breast cancer cells and tissues and regulates breast cancer biological functions, such as proliferation, migration, invasion, and apoptosis [ 18 ]. Besides, Wang et al study found that the strong expression of hsa_circRNA_002178 was detected in exosomes from the plasma of lung adenocarcinoma patients and may serve as a biomarker for the early diagnosis of lung adenocarcinoma [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…hsa_circ_002178 exerts its function by binding miR-1258 to upregulate KDM7A. The expression of circRNA circ_002178 correlates with the survival rate, tumor size, lymph node metastasis, and TNM stage of tumor patients [ 149 ].…”
Section: Biology Of Cscs and Their Interaction With Tumor Microenviro...mentioning
confidence: 99%